ANALISA PENGARUH ASIMETRI INFORMASI DAN MANAJEMEN LABA TERHADAP COST OF EQUITY CAPITAL - Siti Ismawati Arofah (2017)
The purpose of this study was to determine the effect of asymmetric information and earnings management on the cost of equity capital. The study uses the sector companies mining of good listed in Indonesia Stock Exchange as a sample. Sampling technique using purposive sampling method.. Selection of a sample of 41 mining companies sector listed in Indonesia Stock Exchange in 2013-2015 resulted in 30 companies that are acceptable. Testing the hypothesis in this study using Multiple Linear Regression Analysis with SPSS 23 and a significance level of 5%. The result of the testing showed that the asymmetric information and earnings management does not signifian effect on the cost of equity capital.